(untitled) (Eurasian Medical Research Periodical, 2022)
The utilization of panoramic radiographs and computed tomography plays an extremely important role in the precise diagnosis, treatment planning, and prognostic evaluation of a wide variety of complex dental pathologies. This is because both of these imaging modalities are capable of producing three-dimensional images. This technique is currently considered the gold standard for imaging the oral and maxillofacial region. Its numerous advantages, which include reductions in exposure time, radiation dose, and cost in comparison to other imaging modalities, have earned it this status. Cone-beam computed tomography is now the method that is universally regarded as the most accurate way to image the oral and maxillofacial regions of the body. Because of this, the practice of dentistry has been completely transformed by the introduction of this technique, which is now the method that is used. This review focuses not only on the widespread application of cone-beam computed tomography in the maxillofacial and dental regions, but also on the upcoming software developments that have the potential to further improve cone-beam computed tomography imaging. In other words, this review examines both the applications of cone-beam computed tomography in the maxillofacial and dental regions, as well as their widespread application. The imaging provided by cone-beam computed tomography stands to benefit in a variety of different ways from the implementation of these new advancements